AN ANALYSIS OF MORPHOLOGICAL AND SYNTACTICAL ERRORS IN RECOUNT TEXT - Noening Poejilestari (STIBA IEC JAKARTA, 2020)
The purpose of this study is to determine the morphological errors and syntactic errors made by students in writing recount text, frequency of errors, types of dominant errors and sources of errors. The research method used is qualitative research. The data from this study are 70 recount texts made by students of tenth grade in SMK Negeri 9 Kota Bekasi. The research found that there were still many mistakes made by the tenth grade students of SMKN 9 in Bekasi in writing English recount text. For morphological errors the researcher found that students made 56 errors which included single errors with the number of errors 4 (7.14%), plural form errors with number of errors 5 (8.93%), errors belonging to the number of errors 8 (14.29%), errors to infinitive with the number of errors 9 (16.07%) and the formation error in the past with the number of errors 30 (53.57%). While for syntactic errors, the researcher found that students made 113 errors which included omission errors with 47 errors (41.60%), addition errors with 24 errors (21.24%) and formation errors with 42 errors (37.16%). This shows that grammar is a weakness of students in writing essays, especially recount text. From the results of the study it was found that students experienced obstacles in writing caused by interlingual factors, intralingual factors and excessive generalization. Thus students' writing skills are still weak.